2020
DOI: 10.1162/qss_a_00007
|View full text |Cite
|
Sign up to set email alerts
|

Co-citations in context: Disciplinary heterogeneity is relevant

Abstract: Citation analysis of the scientific literature has been used to study and define disciplinary boundaries, to trace the dissemination of knowledge, and to estimate impact. Co-citation, the frequency with which pairs of publications are cited, provides insight into how documents relate to each other and across fields. Co-citation analysis has been used to characterize combinations of prior work as conventional or innovative and to derive features of highly cited publications. Given the organization of science in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A different approach is used by Boudreau, Guinan, et al (2016) and Carayol, Lahatte, and Llopis (2017), who used unusual combinations of keywords for measuring novelty. Other studies in the area of measuring novelty have been published by Foster, Rzhetsky, and Evans (2015), Mairesse and Pezzoni (2018), Bradley, Devarakonda, et al (2020), andWagner, Whetsell, andMukherjee (2019), each with a different focus. According to the conclusion by Wang et al (2018), "prior work suggests that coding for rare combinations of prior knowledge in the publication produces a useful a priori measure of the novelty of a scientific publication" (p. 1074).…”
Section: Indicators Measuring Disruptionmentioning
confidence: 99%
“…A different approach is used by Boudreau, Guinan, et al (2016) and Carayol, Lahatte, and Llopis (2017), who used unusual combinations of keywords for measuring novelty. Other studies in the area of measuring novelty have been published by Foster, Rzhetsky, and Evans (2015), Mairesse and Pezzoni (2018), Bradley, Devarakonda, et al (2020), andWagner, Whetsell, andMukherjee (2019), each with a different focus. According to the conclusion by Wang et al (2018), "prior work suggests that coding for rare combinations of prior knowledge in the publication produces a useful a priori measure of the novelty of a scientific publication" (p. 1074).…”
Section: Indicators Measuring Disruptionmentioning
confidence: 99%
“…Novel, atypical, or otherwise unusual combinations of cocited articles have been explored at the journal level (Boyack & Klavans, 2014;Bradley, Devarakonda, et al, 2020;Uzzi, Mukherjee, et al, 2013;Wang, Veugelers, & Stephan, 2017). However, journal-level classifications have limited resolution relative to article-level studies, which may better represent the actual structure and aggregations of the scientific literature (Gómez, Bordons, et al, 1996;Klavans & Boyack, 2017;Milojevic, 2019;Shu, Julien, et al, 2019;Waltman & van Eck, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In closing, this study primarily concerned examining immunology publications and others connected to them by citation. Other studies have shown that citation behavior can depend significantly on the field (Bradley, Devarakonda, et al, 2020;Wallace, Larivière, & Gingras, 2012), making extrapolation of trends from one field to another premature. Thus, the trends in this study may not be consistently found in other research disciplines or time frames.…”
Section: Discussionmentioning
confidence: 99%